Studien zur Geschichte und Archäologie des byzantinischen Cherson - Romancuk, Alla, (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
The book is the first in a Western European language to present the results of the excavation of Byzantine Cherson (7th-14th centuries) in the Crimea. It offers a comprehensive study of the topography of the city, its material culture, everyday life, architecture, craft production, and religious beliefs. Taking all archaeological, written and other evidence into account, it places Cherson within the overall history of the Byzantine Empire, its periphery and Black Sea-Mediterranean trade.